KAJIAN MEDIA INFORMASI PANEL DISPLAY PADA PAMERAN MUSEUM BANK INDONESIA - Ignatius Soekarno Hartanto; Ahadiat Joedawinata; Sangayu Ketut Laksemi Nilotama (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2020)
The Study Of Information Media Panel Display At Museum Bank Ndonesia. Excellence in terms ofeducation for visitors is manifested by the Bank Indonesia Museum in the form of exhibitions thatrepresent real places or places where historical events have occurred. Of course visitors and visitors justwalk around and have a look, in terms of education. Various forms of exhibition display are designed anddepicted diachronic (timeline), through visual displays and display panels containing narratives thatguide visitors around to find information conveyed by the Bank Indonesia Museum. The uniquenessof the visual information pattern from the panel display in the Bank Indonesia Museum exhibition isinteresting to be appointed as the object of research, because the information in the form of narrativestories from Bank Indonesia is conveyed and described in detail in the panels used.Consideration in achieving this, an approach is made through graphic design studies with regardto information design and editorial design. The initial step of observation is in the field, by lookingat and sorting out the tendency of the panel displays used in conveying information in the form ofnarratives and literature studies carried out as a theoretical basis relating to museums and exhibitions,media, information, graphic information media, etc. The next stage is an analysis of visual informationpatterns from the display panel of the Bank Indonesia Museum which is carried out based on a graphicdesign approach with regard to information design and editorial design. The approach used is set onthe arrangement of grid patterns, hierarchies of information, utilization of graphic processing, andutilization of narrative forms of information.From the graphic design approach revolving around information and editorial design with regard toexhibitions, it was found that the display pattern of the exhibition’s visual information panel that enteredthe Museum Bank Indonesia exhibition had a clear and structured hierarchy of information delivery,continuous graphic display with the narrative found, and Arrangement and utilization of media size orlayout between narrative content and graphic processing content.